La systémique agraire à l'Inra Histoire d'une dissidence - Cornu, Pierre (éditions Quae, 2021)
Based on original research, combining archives and oral testimonies, this work traces, from the first trial and error of systemic approaches in the 1960s to the turning point of sustainable development in the 2000s, the history of the department Sad - Agrarian systems and development - from INRA (now INRAE). From its origins, Sad has been characterized by its distancing from agricultural modernization, conceived as an enterprise of rationalization and technical and economic optimization. Present in the fragile areas of agrarian abandonment, Sad will be no less concerned about the future of large-scale farming areas plagued by doubts about the virtues of intensification. The "Sadians", in all their diversity and contradictions, will constantly question the scientific standards in force. They will thus help to stimulate the scientific and societal debate on the issues of family farming, the quality of production, environmental services or the heritage dimension, both natural and cultural, of agriculture. Nourished by their own research, but also by sharing experience on an international scale, the theoretical and methodological daring of the Sadians will not leave anyone indifferent, at INRA and outside. This book tells us how they went in thirty years from dissent and marginality to a scientific contribution fully recognized within research French agronomic. At the crossroads of the history of the present, the history of science and the philosophy of science, the author highlights the individuals - technicians, engineers, scientists and teachers - who have made a deeply original contribution to intellectual matrix of French and international agricultural research.